2023
DOI: 10.1002/adfm.202311370
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hydrazine Electro‐Oxidation Achieved by Tailored Electron Injection into Fe (III) Sites Activating Dehydrogenation

Shucong Zhang,
Xiaotong Wei,
Shuixing Dai
et al.

Abstract: Tailoring the d‐orbital electron of Fe (III) in oxyhydroxide is highly expected to realize an efficient hydrazine oxidation reaction (HzOR) for assisting seawater electrolysis. Although interface engineering can effectively change electron states on Fe sites by charge injection or extraction, most interfaces have a directional electric field for inaccessible regulation. Herein, the combination of iron oxyhydroxide and biphasic nickel phosphide is established to obtain a dual built‐in electric field (BEF) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…Altering the heterostructure components is one effective means of manipulating BEF, but its uncontrollable factors increase the difficulty of regulating BEF. 27 To address these challenges, transition metal sulfides (TMSs), such as Ni 3 S 2 , MoS 2 , and CoS 2 , are preferred due to their unique electronic structure, abundant modulation strategies, and cost-effectiveness. 28−31 Meanwhile, metal oxides/hydroxides are considered to be an ideal candidate for stable OER catalysts, which are the thermodynamically…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altering the heterostructure components is one effective means of manipulating BEF, but its uncontrollable factors increase the difficulty of regulating BEF. 27 To address these challenges, transition metal sulfides (TMSs), such as Ni 3 S 2 , MoS 2 , and CoS 2 , are preferred due to their unique electronic structure, abundant modulation strategies, and cost-effectiveness. 28−31 Meanwhile, metal oxides/hydroxides are considered to be an ideal candidate for stable OER catalysts, which are the thermodynamically…”
Section: ■ Introductionmentioning
confidence: 99%
“…Related studies have found that coupling materials with different work functions (WFs) may induce the built-in electric field (BEF) that triggers the directional movement of electrons to form local electron-rich/deficient regions, which is conducive to the inhibition of overoxidation and the optimization of adsorption. Inspired by this, it is expected that rationally designing and regulating the BEF will facilitate the asymmetric distribution of charge, thereby realizing the precise modulation of the charge density for Ru atoms with exceptional resistance to overoxidation and the appropriate binding capacity of OER intermediates. Altering the heterostructure components is one effective means of manipulating BEF, but its uncontrollable factors increase the difficulty of regulating BEF . To address these challenges, transition metal sulfides (TMSs), such as Ni 3 S 2 , MoS 2 , and CoS 2 , are preferred due to their unique electronic structure, abundant modulation strategies, and cost-effectiveness. Meanwhile, metal oxides/hydroxides are considered to be an ideal candidate for stable OER catalysts, which are the thermodynamically favorable end point for most metals under OER high oxidative conditions with low transient dissolution, thus avoiding structural variations and instability during the OER process. , Furthermore, the reported NiMoO x /NiMoS, NiS 2 /NiO@N−C/NFs, and NiFe(OH) x -Ni 3 S 2 /NF heterostructures indicate that catalysts consisting of TMSs and metal oxides/hydroxides can significantly modulate the interface electronic property and accelerate OER kinetics with the lowered reaction barrier. , …”
Section: Introductionmentioning
confidence: 99%